THE POWER OF INTERACTIVE TECHNIQUES IN MUSIC EDUCATION (Academia Science Repository, 2023)
This article explores the transformative power of interactive techniques in music education, encompassing active music listening, creative music making, ensemble performance, technology integration, multisensory approaches, reflective practice, cultural exploration, performance and presentation skills development, and social-emotional development. It discusses the benefits of these techniques in engaging students actively in the learning process, enhancing their musical skills, fostering creativity, developing critical thinking and collaboration skills, promoting cultural understanding, and supporting social-emotional growth.